2019
DOI: 10.3389/fneur.2019.00908
|View full text |Cite
|
Sign up to set email alerts
|

Adult Stem Cells and Induced Pluripotent Stem Cells for Stroke Treatment

Abstract: Stroke is the main cause of disability and death in the world within neurological diseases. Despite such a huge impact, enzymatic, and mechanical recanalization are the only treatments available so far for ischemic stroke, but only <20% of patients can benefit from them. The use of stem cells as a possible cell therapy in stroke has been tested for years. The results obtained from these studies, although conflicting or controversial in some aspects, are promising. In the last few years, the recent development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 103 publications
0
23
0
Order By: Relevance
“…Implantation of modified bone marrow-derived mesenchymal stem cells (SB623) transiently transfected with the human Notch-1 intracellular domain in a patient with stable chronic stroke is safe and is accompanied by improvements in clinical outcomes [61]. It is now well established that there is no engraftment of MSCs in the brain after intravenous administration and the recovery effects observed in some ischemic animal models are mediated by factors secreted by MSCs [62]. Recently, extracellular vesicles released by MSCs or NSCs are recognized as effective in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Implantation of modified bone marrow-derived mesenchymal stem cells (SB623) transiently transfected with the human Notch-1 intracellular domain in a patient with stable chronic stroke is safe and is accompanied by improvements in clinical outcomes [61]. It is now well established that there is no engraftment of MSCs in the brain after intravenous administration and the recovery effects observed in some ischemic animal models are mediated by factors secreted by MSCs [62]. Recently, extracellular vesicles released by MSCs or NSCs are recognized as effective in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in animal models of stroke have shown that MSC treatment has beneficial effects on stroke recovery; however, contradictory results have also been reported [ 16 ]. The majority of in vitro and in vivo studies have been performed on rodent and human BM-MSCs, while human-derived ASCs are less studied [ 15 ]. Here, ASCs were cocultured on inserts with SH-SY5Y- and hiPSC-neurons after OGD for 24 or 72 h. The results showed that ASC coculture increased cell viability and decreased cytotoxicity and cell death in both cell models.…”
Section: Discussionmentioning
confidence: 99%
“…Transplantation of mesenchymal stem cells (MSCs) represents a new potential therapeutic strategy for stroke [ 15 ]. In previous in vivo animal studies, transplantation of MSCs has been shown to promote functional recovery and reduce lesion size [ 16 , 17 ], and these cells have already been utilized in clinical phase studies with varying results [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the administration of fasudil-loaded liposomes under occlusion ameliorated the injury associated with reperfusion by rt-PA. 164) Xu et al developed a multifunctional formulation called "nanoplatelets" for sequential selective delivery of rt-PA and neuroprotectant to ischemic sites. 165) Those neuroprotectant-loaded nanoparticles with thrombin-cleavable Tat peptide-coupled rt-PA can deliver rt-PA to thrombi and enhance migration to ischemic sites.…”
Section: Ischemic Strokementioning
confidence: 99%
“…The current status and details of exogenous stem cell transplantation are summarized in other reviews. 166,167) Endogenous NSC activation is receiving increased attention because it does not require the processing of living cells. Some therapeutic systems have been developed in combination with DDS techniques.…”
Section: Ischemic Strokementioning
confidence: 99%